The Era of Marine Environmental Regulations: HMM and Maersk's Response Strategies (aSSIST Business Review, 2025)
Globally, environmental issues have emerged as a core challenge that must be addressed for sustainable development. The shipping industry handles approximately 90% of the world's cargo volume and faces environmental challenges due to its large-scale emissions of greenhouse gases and pollutants. Specifically, the International Maritime Organization (IMO) and the European Union (EU) are strengthening various environmental regulations to reduce the shipping industry's environmental impact. These include the MARPOL Convention, FuelEU Maritime, the Energy Efficiency Design Index (EEDI) and Energy Efficiency Existing Ship Index (EEXI), the Carbon Intensity Indicator (CII), the Emissions Trading System (ETS), and the Carbon Border Adjustment Mechanism (CBAM). These regulations offer shipping companies opportunities beyond mere legal compliance, driving technological innovation and competitive realignment.This study compares and analyzes the approaches to environmental regulations pursued by HMM and Maersk, two global shipping companies with contrasting strategies. HMM has secured flexibility advantageous for entering emerging markets by diversifying its technologies, concurrently developing various alternative fuel technologies such as LNG, methanol, and ammonia. Additionally, it is actively pursuing digital twin-based operational efficiency improvements to comply with regulations like the IMO's CII. Conversely, Maersk is focusing its investments on methanol propulsion technology to lead in standardization, while concentrating on building a global production-supply value chain to respond to the EU ETS and FuelEU Maritime.The strategic divergence between the two companies illustrates a dichotomous approach of flexibility versus efficiency in responding to environmental regulations, suggesting that the shipping industry can leverage regulations not merely as constraints but as tools for innovation and enhanced competitiveness. This study is expected to provide practical implications for strategy formulation and policy design by small and medium-sized shipping companies through comparative analysis across technological, financial, and collaborative ecosystem dimensions.
Keywords: Climate change; eco-friendly shipping; greenhouse gases; IMO; EEDI; EEXI; CII; ETS; CBAM; MARPOL; FuelEU Maritime